Critério diagnóstico da doença meningocócica na Região Metropolitana de Campinas, São Paulo, Brasil Meningococcal disease diagnostic criteria in Greater Metropolitan Campinas, São Paulo State, Brazil - Maria Rita Donalisio; Marilu Mendes Moscardini Rocha; Raquel Maria Ferreira Ramalheira; Brigina Kemp (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2004)
Foi estudado o critério de confirmação etiológica: cultura, clínico, teste do Látex e contraimunoeletroforese, exame bacterioscópico e clínico/epidemiológico dos 568 casos notificados de doença meningocócica na Região Metropolitana de Campinas, São Paulo, Brasil, de 1993 a 2002. Foram analisadas as variáveis: forma clínica, idade, sexo, local de moradia e internação, época do ano de ocorrência, letalidade e sorogrupo da Neisseria meningitidis. Confirmaram-se, pela cultura, 68,7% dos casos. A letalidade foi diferente de acordo com o critério de confirmação da doença. As formas clínicas: meningite sem meningococcemia (OR = 2,87; IC: 1,89-4,38) e a meningococcemia sem meningite (OR = 0,26; IC: 0,17-0,45) mostraram-se associadas com o critério cultura. Maior atenção à confirmação diagnóstica deve ser dada aos casos mais severos. A utilização do teste da reação em cadeia de polimerase pode ser útil para aumentar a capacidade da confirmação etiológica da doença meningocócica em casos de culturas negativas. The aim of this article is to evaluate confirmatory criteria: culture, latex agglutination, counter immunoelectrophoresis, microscopic examination, and clinical/epidemiological criteria for cases of meningococcal disease reported in Greater Metropolitan Campinas, São Paulo State, Brazil, from 1993 to 2002 (568 cases). The following variables were also studied: clinical features, gender, age, city, hospital, case fatality, seasonality, and Neisseria meningitidis serogroup. Culture as a confirmatory criterion was the dependent variable in univariate analysis. The mean proportion of confirmatory criterion by culture was 68.7%. Clinical features of meningococcal disease - meningitis without septicemia (OR = 2.87; CI: 1.89-4.38) and septicemia without meningitis (OR = 0.26; CI: 0.17-0.45) - were associated with confirmation by culture. Case fatality rates were different among all diagnostic criteria. More attention should be given to etiological diagnostic confirmation in more severe cases. Diagnostic methods such as PCR may improve etiological confirmation of meningococcal disease in cases with negative cultures.